2022
DOI: 10.1002/cncr.33965
|View full text |Cite
|
Sign up to set email alerts
|

Patient navigation to address sociolegal barriers for patients with cancer: A comparative‐effectiveness study

Abstract: BACKGROUND: Sociolegal barriers to cancer care are defined as health-related social needs like affordable healthy housing, stable utility service, and food security that may be remedied by public policy, law, regulation, or programming. Legal support has not been studied in cancer care. METHODS: The authors conducted a randomized controlled trial of patients who had newly diagnosed cancer at a safetynet medical center in Boston from 2014 through 2017, comparing standard patient navigation versus enhanced navig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 65 publications
1
36
0
Order By: Relevance
“…The recommended strategies provided by respondents in this study align with several World Health Organization (WHO)-identified actionable priorities to enhance continuity and coordination of care [ 99 ]. The concept of a patient navigator should be considered [ 56 ]. The navigator may also assist with monitoring and facilitating the patient’s care [ 100 , 101 , 102 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommended strategies provided by respondents in this study align with several World Health Organization (WHO)-identified actionable priorities to enhance continuity and coordination of care [ 99 ]. The concept of a patient navigator should be considered [ 56 ]. The navigator may also assist with monitoring and facilitating the patient’s care [ 100 , 101 , 102 , 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research focusing on health care delivery has revealed the complexity of coordinating care for people with cancer and proposes some promising interventions [ 54 , 55 ]. Recent studies and reviews on cancer care coordination interventions have found that patient navigation, designated care coordinators, and collaborative care models are among the common approaches implemented [ 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Multiple barriers to improving the provision of cancer care exist, including lack of social support, financial concerns, and problems with healthcare communications; in this context, effective care coordination is required [ 8 , 12 , 24 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ].…”
Section: Study Backgroundmentioning
confidence: 99%
“…The median number of participants per study was 127 (range, 626). Among the 27 6,7,15,16,[19][20][21][22][23][24][25][26][27][28][29][30][36][37][38][39][40][41][42][43][44][45][46] studies reporting the mean or median age of the participants, the pooled average age was 56 6 12 years. Furthermore, 14 studies reported the insurance status of their participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…These initiatives seek to enhance health care accessibility by encouraging early detection and screening, 5 increasing treatment adherence, 6 and eliminating barriers to the efficient delivery and receipt of optimal cancer care. 7 However, there are gaps in our understanding of the most effective design and implementation of interventions that could be widely disseminated to alleviate the burden of cancer-related health disparities, especially among marginalized racial and ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Battaglia et al 12 analyzed standard patient navigation versus navigation supported by legal advocacy to specifically address barriers like unstable housing, utility services, and food insecurity. They report that almost all patients in both groups experienced the same levels of distress and needs, received timely care, and reported satisfaction.…”
Section: Introductionmentioning
confidence: 99%